QUALITY IMPROVEMENT THROUGH ACCREDITATION AT GRADUATE STUDIES UIN-SU MEDAN - Hasan Asari; Hafsah Hafsah; Yusnaili Budianti (State Islamic University North Sumatra, 2018)
Abstract: This article elaborates institutions of quality assurance and accreditation of departments in the context of quality improvement at Graduate Studies of UIN-SU Medan. This qualitative research discovered the following: First, the Quality Assurance Unit of the Graduate Studies, which was established in 2016, has not been operational mainly due to lack of competence of its personnel and insufficient fund. Second, the main hindrances in accreditation process are poor understanding of departments’ management, limited support from stakeholders, and insufficient funding. The ‘mentoring’ of UIN-SU Medan Quality Assurance Office could not have been more helpful and indeed has solved some of the problems. However this practice has not been so useful in developing internal quality assurance culture. Despite the fact that its departments have undergone two to three accreditation procedures, the Graduate Studies has not been successful in delivering a better result.Abstrak: Peningkatan Mutu Melalui Akreditasi Pada Pascasarjana UIN-SU Medan. Artikel ini menganalisis kelembagaan penjaminan mutu dan pelaksanaan akreditasi program studi dalam konteks peningkatan mutu pendidikan di lingkungan Pascasarjana UIN-SU Medan. Penelitian yang menerapkan prosedur penelitian kualitatif ini menemukan: Pertama, Unit Penjaminan Mutu Pascasarjana yang dibentuk tahun 2016 tidak operasional karena tidak sesuainya kompetensi personel yang ditempatkan serta tidak tersedianya dukungan finansial. Kedua, kesulitan utama dalam proses akreditasi adalah pemahaman pengelola Program Studi tentang akreditasi yang sangat variatif; rendahnya budaya mutu sivitas akademika; dan terbatasnya dukungan finansial. Pendampingan dari Lembaga Penjaminan Mutu UIN-SU Medan sangat membantu. Sayangnya pendampingan ini, meskipun menyelesaikan masalah secara ad hoc tetapi tidak mendukung berkembangnya budaya penjaminan mutu internal yang baik. Dengan berbagai persoalan yang ada, peringkat akreditasi Program Studi di lingkungan Pascasarjana UIN-SU Medan belum mengalami peningkatan meskipun masing-masing Program Studi sudah menjalani dua atau tiga kali akreditasi.Keywords: PTKIN, penjaminan mutu, akreditasi